ANALISIS KINERJA KEUANGAN PADA BUMDES DESA RANTAU PANJANG KABUPATEN ROKAN HULU - Saripah Ainun; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the financial performance of BUMDes in Rantau Panjang Village, Rokan Hulu Regency for the periode 2017 to 2021 by using likuidity, solvency, profitability, and activity ratios. The type of research conducted is in the form of secondary data, which is data from BUMDes financial data of the BUMDes of Rantau Panjang Village, Rokan Hulu Regency, it was concluded that the level of liquidity in 2017 to 2021 in terms of the current ratio had not good results and cash ratio had not good results. In terms of solvency from 2017 to 2021, in terms of DAR and DER, the results are very good. In terms of the profitability ratio for 2017 to 2021, ROA has obtained quite good result and ROE has received poor results. The level of activity in 2017 to 2021 in terms of Working capital turnover, Receivable turnover and Total asset turnover showed not good results. Keywords : Financial Performance, Likuidity,Solvency,Profitability and Activity.